Eutanasia y derechos fundamentales = Euthanasia and fundamental rights - Viganò, Francesco (Política criminal, 2023)
Every legal regulation of the different forms of euthanasia necessarily raises questions of compatibility with fundamental rights (e.g., the right to life, bodily integrity, private life, personal free development, and autonomy) and with the super-principle of human dignity. Such questions have been intensively discussed by the courts all over the world during the last decades. This paper examines some of the most significant decisions by constitutional and supreme courts, as well as by the European Court of Human Rights, that in many cases have modified (or contributed to) the state of the law on euthanasia, for the sake of protecting the patient’s fundamental rights, even against the will of democratically elected legislators.